Definite Integrals Involving Logarithmic Powers, Binomials and Polynomials Expressed in terms of the Lerch Function (European Journal of Pure and Applied Mathematics, 2022)
Closed expressions using the Lerch function for a definite integral are derived and evaluated. Some of these closed expressions are given in Gradshteyn and Ryzhik. Some special cases of the integral are derived and discussed. The majority of the results in this work are new.
Keywords: entries of Gradshteyn and Ryzhik; Lerch function; analytic continuation